2008
DOI: 10.1097/md.0b013e31818ec711
|View full text |Cite
|
Sign up to set email alerts
|

Acute Viral Infections in Patients With Systemic Lupus Erythematosus

Abstract: Few studies have evaluated the impact of viral infections on the daily management of patients with systemic lupus erythematosus (SLE). We analyzed the etiology and clinical features of acute viral infections arising in patients with SLE and their influence on the diagnosis, prognosis, and treatment of SLE. Cases occurring within the last 5 years were selected from the databases of 3 large teaching hospitals. Acute viral infections were confirmed by the identification of specific antiviral IgM antibodies and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(112 citation statements)
references
References 61 publications
2
98
0
12
Order By: Relevance
“…Due to the paradoxically low prevalence of SLE in western Africa (a high prevalence would be expected because African ancestry is an established risk factor for SLE), it has been hypothesized that environmental endemic infections, such as malaria, can modulate the immune response and provide protection against SLE and other autoimmune disorders (26). On the other hand, infectious agents, such as parvovirus B19, cytomegalovirus, and Epstein-Barr virus, have been associated with the development of SLE (27,28). Occupational and everyday exposures, such as ultraviolet light, smoking, silica, insecticides, and certain solvents (paints, dyes, nail applications), have also been linked to SLE development (1,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the paradoxically low prevalence of SLE in western Africa (a high prevalence would be expected because African ancestry is an established risk factor for SLE), it has been hypothesized that environmental endemic infections, such as malaria, can modulate the immune response and provide protection against SLE and other autoimmune disorders (26). On the other hand, infectious agents, such as parvovirus B19, cytomegalovirus, and Epstein-Barr virus, have been associated with the development of SLE (27,28). Occupational and everyday exposures, such as ultraviolet light, smoking, silica, insecticides, and certain solvents (paints, dyes, nail applications), have also been linked to SLE development (1,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Ramos-Casals et al [4] analyzed the aetiology and clinical features of acute viral infections arising in patients with SLE and their influence on the diagnosis, prognosis, and treatment of SLE. The authors concluded that more proactive investigation of acute viral infections in SLE patients presenting with fever is desirable.…”
Section: Non-bacterial Infectionmentioning
confidence: 99%
“…Moreover, some infections may produce a systemic infection mimicking SLE, either superimposed or trigger a flare [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical pictures are wide: pneumonia and alveolar hemorrhage, skin ulcers, proteinuria and renal failure, thrombocytopenia, pancytopenia, hepatitis, vasculitis, retinitis and encephalitis. It may be underseeked and hence underdiagnosed but only few cases with any of these complications are reported in SLE (Ramos-Casals et al, 2008). Diagnosis of CMV is made with serology, although a note of caution should be taken: false positive reactions are not infrequent, presumably because of secondary production by auto-reactive B-cells.…”
Section: Opportunistic Infections Of Viral Originmentioning
confidence: 99%
“…Some authors have demonstrated activation of immune system and antibodies production during acute viral infections, as we mentioned before. On the other hand, besides its suggested pathogenic role in autoimmune diseases, acute viral infections are frequently reported as partners of disease flares or at disease presentation, confusing and favoring misinterpretation of clinical signs and deferral of adequate treatment (Ramos-Casals et al, 2008). Herpes zoster (HZ) is the symptomatic reactivation of the varicella-zoster virus (VZV), an infection frequently acquired at childhood; virus prevails in a latent stage in the dorsal root ganglia for long periods of time; more than 90% of adults have serologic evidence of a previous VZV infection.…”
Section: Opportunistic Infections Of Viral Originmentioning
confidence: 99%